STUDY OF THE DISTRIBUTION PROFILE OF MECHANISMS GLAND WITH IMPLANTATION METHOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article on ions with the (110) orientation were implanted into the silicon single crystal. Using the RBS (Rutherford backscattering) method, in combination with channeling, the distribution profiles of the embedded impurity were studied; in addition, the distribution profiles of radiation defects located in the crystal lattice were studied. The simulation results in the TRIM (to’liq nomi kerak) program are compared with the experimental results. It is shown that, at an energy of 4.6 keV / nucleon, a coincidence of the average projective ranges is observed, and when the energy falls to 1.6 keV / nucleon, a difference of 35% is observed. The dose dependence is not taken into account correctly at an energy of 1.6–4.6 keV / nucleon.